Analysis of the Influence of Banking Product Knowledge on Intention to Use Banking Products - Frans Sudirjo; Arnold Sultantio Hutabarat; Ratnawita; Zunan Setiawan; Rubait Dasururi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Sharia banking is banking that uses principles that are in accordance with the Islamic religion. In the development of Islamic banking, from the year it was found that it was quite extensive so that it could reach remote areas in terms of knowledge. The purpose of this researcher is to conduct a theoretical test of the effect of knowledge of Islamic banking products on interest in becoming a customer. This research method uses quantitative with simple regression analysis technique which is tested on 100 respondents from those taken using purposive random sampling technique. The results of the partial t test research can be concluded temporarily that knowledge has a significant effect on the intention to become a customer of Islamic banking, because from the results of the t test the value of t count > t table. For the hypothesis with the f test the result is that knowledge has a significant effect on the intention to become a customer of Islamic banking because the f count > f table and the significant value is below 0.05.